2018
DOI: 10.3390/nu10060695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Frozen Storage on Phospholipid Content in Atlantic Cod Fillets and the Influence on Diet-Induced Obesity in Mice

Abstract: A large fraction of the n-3 polyunsaturated fatty acids (PUFAs) in cod fillet is present in the form of phospholipids (PLs). Freezing initiates hydrolysis of the PLs present in the fillet. Here, we compared the effects of Western diets based on frozen cod, fresh cod or pork with a diet based on casein in male C57BL/6J mice fed for 12 weeks at thermoneutrality. Diets based on fresh cod contained more PL-bound n-3 PUFAs (3.12 mg/g diet) than diets based on frozen cod (1.9 mg/g diet). Mice fed diets containing po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…However, we recently demonstrated that addition of phospholipid-bound, but not TAG-bound, n -3 PUFA to a pork-based diet led to a small increase in weight gain ( 113 ) . Further, freezing initiates hydrolysis of the phospholipids present in the fillet, but the anti-obesogenic effect of frozen stored cod was more pronounced than fresh cod ( 113 ) . Still, feeding mice Western diets where meat from lean pork was exchanged with stored frozen cod for 12 weeks lowered the n -6: n -3 ratio in liver phospholipids and in erythrocytes ( 100 ) .…”
Section: Animal Trials With Lean Seafood Obesity and Potential Mechamentioning
confidence: 99%
“…However, we recently demonstrated that addition of phospholipid-bound, but not TAG-bound, n -3 PUFA to a pork-based diet led to a small increase in weight gain ( 113 ) . Further, freezing initiates hydrolysis of the phospholipids present in the fillet, but the anti-obesogenic effect of frozen stored cod was more pronounced than fresh cod ( 113 ) . Still, feeding mice Western diets where meat from lean pork was exchanged with stored frozen cod for 12 weeks lowered the n -6: n -3 ratio in liver phospholipids and in erythrocytes ( 100 ) .…”
Section: Animal Trials With Lean Seafood Obesity and Potential Mechamentioning
confidence: 99%
“…Given that a large fraction of the n-3 PUFAs in cod fillets is present in phospholipids, our results are in line with the reported higher bioavailability of PL-bound relative to TAG-bound EPA and DHA [ 20 , 21 , 22 , 23 , 25 ]. However, it has also been reported that dietary PL-bound n-3 PUFAs and TAG-bound n-3 PUFAs have similar bioavailability [ 19 ] and a critical review published in 2014 concluded that there was no evidence for greater bioavailability of n-3 PUFAs from PLs compared with TAGs [ 48 ]. Still, results from this study are in line with other studies demonstrating that an increased n-3:n-6 ratio in fish fillets and in PLs from livers and RBCs collected from mice consuming fish-containing diets, associates with reduced obesity [ 24 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The methyl ester of C19:0 (non-adecanoic acid) was added to each fraction/sample as the internal standard before saponifying the lipid samples with NaOH and methylating the fatty acids using 12% BF 3 in methanol. Fatty acids in each fraction were determined by a gas chromatography (GC) (GLC TRACE GC 2000, Thermo Fisher Scientific, Waltham, MA, USA) column (CP-sil-88, 50 m WCOT) coupled with a flame ionization detector, identified by retention time using standard mixtures of methyl esters (Nu-Chek Prep, Elysian, MN, USA) and quantified towards the internal standard under conditions as previously described [ 19 ] based on Lie et al [ 17 ]. Limit of quantification was 0.01 mg fatty acids/g sample.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations